Marketing Events Mediating BEV Features and Operating Costs: Impact on Purchase Intentions - Mustafa, Faiz; Santosa, Perdana Wahyu (SAN Scientific, 2024)
This research aims to find out the lack of influence of Batery Electric Vehicle (BEV) features and vehicle operating perspective costs on the interest in purchasing electric cars with marketing events as a mediation and review from an Islamic. This devotional population is a society over 21 years old that is domiciled in Jabodetabek. The sample in this study was made up of people who drove more than three times in one week, for a total of 100 respondents. The sampling technique uses a non-probability method with purposive sampling techniques through the distribution of questionnaires with Google forms. The analytical method used is the Partial Least squares Structural Equation Modeling method (PLS-SEM). The results of the study show that Feature influences Purchase Intention, Feature influences Marketing Event, Vehicle Operating Cost influences Purchase Intention, Marketing Event influences Purchase Intentions, Marketing Event mediates the influence of Feature on Purchase Intentions, Features, Vehicle Operating Costs, Marketing Events, and Purchase Intention BEV cars among the people in Jabodetabek. The implications of the results of this study present that purchase intention towards BEVs encourages producer management to optimally utilize all the variables analyzed in this study proportionally.